Development of Online Directory of Aerospace Engineering Teaching Institutions and Teachers in India - Singh, K.P.; Negi, Nandi (DESIDOC Journal of Library & Information Technology, 2010)
Directory is the vital reference tool for finding information related to organisations, institutions, companies, persons, etc. These sources are becoming more beaming and significant for the users when they are available in e-form and accessible online. The present study is an outcome of a major research project awarded and funded by the Aeronautics Research and Development Board (AR&DB), DRDO, to the Department of Library and Information Science, University of Delhi. Data for the directory was collected through a specially designed ‘Data Capturing Form’ from all the teachers and teaching institutions of Aerospace Engineering in India. The collected data was scrupulously analysed, organised, validated and then used for the development of online directory. The directory is developed on a specially designed Content Management Software (CMS)-based system for managing the content in dynamic environment. DOI: 10.14429/djlit.30.461